2008
DOI: 10.1007/s11664-008-0560-y
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Thermal Fatigue Properties of Sn-Ag-Cu Lead-Free Solder Interconnects on Casio’s Wafer-Level Packages Based on Morphology and Grain Boundary Character

Abstract: Thermal fatigue properties of commercial LF35 (Sn-1.2Ag-0.5Cu-0.05Ni), SAC105 (Sn-1Ag-0.5Cu), and SAC305 (Sn-3Ag-0.5Cu) solders on CasioÕs wafer-level packages are discussed from the viewpoints of both morphology and grain boundary character. Orientation imaging microscopy revealed that both LF35 and SAC305 resisted the coarsening of tin grains during thermal fatigue as compared with SAC105, correlating with their greater fraction of coincidence site lattice boundaries. This seems to explain why LF35 has super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Since crystal orientations of leadfree solder appear to be randomly distributed, each solder joint has a unique microstructure and mechanical response. [3][4][5][6][7][8] Thus, it is important to understand how crystal orientation affects deformation mechanisms and microstructural evolution. 9 It has been widely reported that recrystallization occurs at the interfaces between solder balls and packages or boards due to high strain energy concentration during thermal cycling.…”
Section: Introductionmentioning
confidence: 99%
“…Since crystal orientations of leadfree solder appear to be randomly distributed, each solder joint has a unique microstructure and mechanical response. [3][4][5][6][7][8] Thus, it is important to understand how crystal orientation affects deformation mechanisms and microstructural evolution. 9 It has been widely reported that recrystallization occurs at the interfaces between solder balls and packages or boards due to high strain energy concentration during thermal cycling.…”
Section: Introductionmentioning
confidence: 99%
“…2b), which is in good agreement with results obtained in previous studies. 11,15,32 This indicates that nucleation of the Sn grains is suppressed because more latent heat of freezing is released during the solidification process due to the high entropy of fusion of tetragonal Sn (14 J/mol K). [33][34][35] However, fast growth of b-Sn dendrites could be achieved with the significant undercooling normally associated with Sn and Sn-rich solder alloys, leading to the few grains present in the solder interconnects.…”
Section: Resultsmentioning
confidence: 99%
“…However, it should be noted that a high-angle grain boundary could be assumed as a potential cracking site (or preferred grain boundary sliding site) due to its high energy. 32 If the high-angle boundary coincides with a high stress concentration area, it will accelerate initiation and propagation of cracks or change the cracking path and corresponding failure mode, leading to fast degradation of solder interconnects. On the contrary, low-energy boundaries (low angle and coincidence site lattice) may contribute to enhance the thermal fatigue properties by suppressing grain boundary sliding due to their low energy.…”
Section: Facilitated Cracking By Anisotropic Thermomechanical Responsmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12][13] However, fatigue cracks are frequently observed in the solder bulk instead of in the interfacial IMCs in Pb-free solder interconnects under thermal cycling tests. 14,15 Therefore, it becomes increasing important to study the orientation, microstructure, and deformation behavior of the Pb-free solder alloy itself to obtain better understanding of the failure modes of solder interconnects. Especially, for finite-element modeling, a solder interconnect should not be assumed to be a homogeneous and isotropic structure, because this cannot represent the actual stress and strain distribution in the solder interconnect without the details of the b-Sn grain shape, number, and corresponding crystallographic orientations.…”
Section: Introductionmentioning
confidence: 99%